A randomized controlled trial of the effectiveness of combinations of 'why to reduce' and 'how to reduce' alcohol harm-reduction communications. (October 2021) - Pettigrew, Simone; Booth, Leon; Jongenelis, Michelle I.; Brennan, Emily; Chikritzhs, Tanya; Hasking, Penelope; Miller, Peter; Hastings, Gerard; Wakefield, Melanie
Highlights: Evidence on the efficacy of population-level alcohol control programs is needed. Combining 'why to reduce' intake with 'how to reduce' messages can be effective. Only some forms of 'how to reduce' messages appear to be effective. Encouraging drinkers to count their drinks can assist them reduce consumption. Abstract: Introduction: Alcohol is a major source of harm worldwide. The aim of this study was to experimentally assess the effects of exposing Australian adult drinkers to combinations of 'why to reduce' and 'how to reduce' alcohol harm-reduction messages. Methods: Three online surveys were administered over six weeks: Time 1 at baseline (n = 7, 995), Time 2 at three weeks post-baseline (n = 4, 588), and Time 3 at six weeks post-baseline (n = 2, 687). Participants were randomly assigned to one of eight conditions: (1) a control condition; (2) a 'why to reduce' television advertisement; (3–5) one of three 'how to reduce' messages referring to the following protective behavioral strategies (PBSs): Keep count of your drinks, Decide how many drinks and stick to it, It's okay to say no; and (6–8) the television advertisement combined with each PBS message individually. Intention-to-treat analyses were conducted to determine effects of condition assignment on changes over time in attempts to reduce alcohol consumption and amount of alcohol consumed. Results: Participants assigned to the 'TV ad' and 'TV ad + Keep count of your drinks PBS' conditions reported significant increases in attempts to reduce alcohol consumption. Only participants assigned to the 'TV ad + Keep count of your drinks PBS' condition exhibited a significant reduction in alcohol consumed (−0.87 drinks per person per week). Conclusions: Well-executed 'why to reduce' alcohol harm-reduction advertisements can encourage drinkers to attempt to reduce their alcohol consumption. These ads may be effectively supplemented by specific 'how to reduce' messages designed to encourage drinkers to monitor their intake.